Análise da rotulagem de diferentes marcas de leite em pó integral comercializados na Cidade de Acari, Rio Grande do Norte (Research, Society and Development, 2020)
The nutritional labeling of food is any and all information contained in the packaging referring to the product that is being displayed on supermarket shelves, in order to inform consumers about the product. In this perspective, this research aimed to analyze the labeling of different brands of powdered milk, marketed in the city of Acari, Rio Grande do Norte. The field research, of the transversal type with quantitative character, was carried out through the application of a specific check list for food labeling, based on the current legislation. The analyzed samples were selected at random in large and small supermarkets in the city of Acari- RN and identified in a confidential way by the letters A, B, C, D and E, respectively. The results obtained from the different brands of whole milk powder marketed in the city of Acari- RN showed satisfactory results, being in full compliance with the legislation in force. Such behavior is totally related to the quality policies adopted by the companies, as well as the presence of inspection by the competent bodies of the Brazilian agricultural sector.